PENGARUH KESADARAN LINGKUNGAN DAN GREEN TRANSPORTATION TERHADAP DAMPAK PEREKONOMIAN - Makatita, Grace Gloria; Ratuna, Maharani; Pertiwi, Dian; Syahzuni, Barlia (Jurnal Riset Akuntansi Politala, 2025)
This Research Aims To Analyze The Influence Of Environmental Awareness And Green Transportation On Economic Impacts. This Research Was Conducted In Kebon Jeruk District, West Jakarta City, Involving 100 Respondents Selected Using The Purposive Sampling Method. The Research Results Show That Environmental Awareness And Green Transportation Simultaneously Influence The Economic Impact. Individually, These Two Variables Also Have A Significant Positive Influence On The Economic Impact. Implementation Of Green Transportation Can Improve Air Quality And Community Welfare. However, To Achieve Optimal Results, Effective Collaboration Between Government, Industry, And Society Is Needed. This Research Provides Implications For Policymakers And Stakeholders To Strengthen The Promotion And Implementation Of Sustainable Transportation To Maximize Positive Economic Impacts.